PENYELESAIAN SENGKETA WANPRESTASI DALAM TRANSAKSI MENGGUNAKAN FITUR PAY LATER PADA MARKETPLACE - Aditya, I Wayan Yogi; Yogantara S, Pande (Kertha Desa, 2022)
The emergence of online or fintech loan providers is caused by changes in people's lifestyles. This innovation can be said to bring benefits to the community because the loan requirements are quite easy so there is no need to go to the bank to apply for a loan, especially the use of paylater as a means of transaction. The journal was written to examine the arrangements as well as the validity and disputes arising.  The method of writing this journal is done in normative juridical. Fintech companies cooperate with various online shopping application platforms or marketplaces such as Shopee, Tokopedia and others that offer payment methods such as Pay Later or payment methods with installments without credit cards or online credit, as borrowers must follow the flow or system of borrowing that is true or valid by choosing a platform that is completely registered and supervised by OJK and incorporated in Indonesian Fintech Association in order to avoid things that can cause losses. The legality of the use of PayLater, can be reviewed the validity of which is first in terms of organizers stipulated in Article 2 POJK Number 77 year 2016 declared as “Other Financial Services Institutions”. Online lending has been officially regulated in the legislation in Indonesia, called The Financial Services Authority Regulation Number 77/PJOK.01/2016 of 2016 about “Information Technology-based Money Lending Services”.